Social supports and depressive symptoms among final year students in UMS, Sabah - Norsimah Dasan; Lim, Chin Fen; Norkiah Arsat; Mohd Mahadzir Rahimi Mohamed Nawi (Pusat Penataran Ilmu Bahasa, Universiti Malaysia Sabah, 2020)
The prevalence of depression among university students, especially final year students is increasing. Social support is undoubtedly very important to prevent psychological ailments. The researchers studied the influence social supports that include family, friend and significant other support on depressive symptoms of final year students in University Malaysia Sabah (UMS), Kota Kinabalu. Final year students from Faculty of Medicine & Health Sciences (FPSK), Faculty of Food Science & Nutrition (FSMP), Faculty of Business, Economics & Accountancy (FPEP), and Faculty of Humanities, Arts & Heritage (FSSK) completed the survey measuring depressive symptoms (Center or Epidemiologic Studies Depression Scale (CES-D)), and social support (Multidimensional Perceived Social Support (MPSS)) through online. Through cluster random sampling, the sample selected was 150 students. Result shows social support from family, and friends were significant predictor of depressive symptoms. However, support from significant other (teacher and romantic partner) was not a significant symptoms predictor of depressive symptoms. Family and friends support can act as a protective factor of depressive symptoms but support from significant other does not. The implication of the study are also discussed